The Changing Tides of Action to Address Ocean Acidification in Maine - Frignoca, Ivy; Kenyon, Heather (Maine Policy Review, 2023)
As carbon dioxide emissions continue to rise worldwide, ocean acidification has become a consequence that threatens both human and natural processes. On a global scale, ocean acidification is relatively well understood. However, the complex ecosystem of the nearshore environment presents challenges for monitoring and addressing ocean acidification. In a state such as Maine, whose communities heavily depend on the health of the coastal environment, understanding this threat becomes critically important. In 2014, Maine’s legislature established a six month study commission to investigate this problem and produce recommendations. The commission proposed a coast-wide monitoring network that could identify and use a common suite of instruments and analytical tools to better understand ocean acidification. The data produced by this network could then be used to inform policy and management decisions. Since the conclusion of the study commission, a number of creative partnerships have emerged in the State. A common theme is evident: the most effective way to advance Maine’s understanding of ocean acidification is to work together. This article explores those partnerships, including the most recent between Friends of Casco Bay, the University of New Hampshire, and Wells National Estuarine Research Reserve. This collaboration is striving to test the accuracy, strengths, and weaknesses of in-situ monitoring technology and laboratory approaches. An ultimate report will recommend the most appropriate monitoring equipment, sampling techniques, and quality assurance protocols that can serve as a guide for researchers, agencies, and institutions up and down Maine’s coast to better monitor ocean and coastal acidification in Maine.
Keywords: ocean acidification